Toscana virus meningitis case in Switzerland: an example of the ezVIR bioinformatics pipeline utility for the identification of emerging viruses. (April 2015) - Cordey, S.; Bel, M.; Petty, T.J.; Docquier, M.; Sacco, L.; Turin, L.; Cherpillod, P.; Emonet, S.; Louis-Simonet, M.; Zdobnov, E.M.; Ambrosioni, J.; Kaiser, L.
Abstract: Toscana virus (TOSV) represents a frequent cause of viral meningitis in the Mediterranean Basin that remains neglected in neighbouring countries. We report a documented TOSV meningitis case in a traveller returning from Tuscany to Switzerland. While routine serological and PCR assays could not discriminate between TOSV and Sandfly fever Naples virus infection, a high-throughput sequencing performed directly on the cerebrospinal fluid specimen and analysed with the ezVIR pipeline provided an unequivocal viral diagnostic. TOSV could be unequivocally considered as the aetiological agent, proving the potential of ezVIR to improve standard diagnostics in cases of infection with uncommon or emerging viruses.